(untitled) (Research, Society and Development, 2023)
The Chandless State Park (PEC) in Acre stands out as a Conservation Unit of great interest for research in the Amazon. Studies in the area cover several biological groups, focusing on the importance of preservation and conservation, as well as the traditional practices of the local community. This study, focused on aquatic entomology, reveals the unique biodiversity of Aquatic Insects in the PEC. Despite this, there is a lack of knowledge about the use and importance of these insects for the local environment. The research adopts a descriptive approach, examining streams at a specific time, highlighting challenges in collections. The results aim to fill knowledge gaps, contributing to the understanding of the ecology of aquatic insects in the region and providing support for conservation strategies in the PEC. It is concluded that understanding the influence of environmental factors on the diversity of these insects is crucial for the conservation of aquatic biota and sustainable decision-making at the site.